2015
DOI: 10.1111/acem.12710
|View full text |Cite
|
Sign up to set email alerts
|

Content Validation of a Novel Screening Tool to Identify Emergency Department Patients With Significant Palliative Care Needs

Abstract: Background: The emergency department (ED) is increasingly used by patients with life-limiting illness. These patients are frequently admitted to the hospital, where they suffer from poorly controlled symptoms and are often subjected to marginally effective therapies. Palliative care (PC) has emerged as the specialty that cares for patients with advanced illness. PC has been shown to reduce symptoms, improve quality of life, and decrease resource utilization. Unfortunately, most patients who could benefit from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
69
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 64 publications
(70 citation statements)
references
References 89 publications
(97 reference statements)
0
69
0
1
Order By: Relevance
“…Clinically recognizing disease prognosis and death trajectories as well as identifying the imminently dying patient were considered important since poorly informed physicians limit their ability to provide optimal, or even adequate, information to patients or families who may need to make difficult decisions. Early screening and rapid palliative care assessment are emerging topics with a growing body of evidence‐based research related to using toolkits and other skills to identify patients appropriate for palliative or hospice care . The topic of the ethnic, spiritual, and cultural aspects around end‐of‐life care and death were considered essential to introduce to residents, accepting that not many EM residencies provide their trainees with what is known about best practices.…”
Section: Resultsmentioning
confidence: 99%
“…Clinically recognizing disease prognosis and death trajectories as well as identifying the imminently dying patient were considered important since poorly informed physicians limit their ability to provide optimal, or even adequate, information to patients or families who may need to make difficult decisions. Early screening and rapid palliative care assessment are emerging topics with a growing body of evidence‐based research related to using toolkits and other skills to identify patients appropriate for palliative or hospice care . The topic of the ethnic, spiritual, and cultural aspects around end‐of‐life care and death were considered essential to introduce to residents, accepting that not many EM residencies provide their trainees with what is known about best practices.…”
Section: Resultsmentioning
confidence: 99%
“…However, we find that meeting the ‘gold standard’ can be aided by lists that reference the concept of ‘futility’ . There are a number of these, one example is represented in Table . Recent research has shown that the use of one such list is acceptable and reliable in the ED setting …”
Section: Initiating Planning In the Patient Approaching End‐of‐lifementioning
confidence: 99%
“…16 There are a number of these, one example is represented in Table 2. [17][18][19][20] Recent research has shown that the use of one such list is acceptable and reliable in the ED setting. 21 Emergency physicians have a critical circuit breaker role in: (i) identifying patients who would benefit from formal advance care planning; and then (ii) raising the issue at the appropriate time in a non-threatening way.…”
Section: Initiating Planning In the Patient Approaching End-of-lifementioning
confidence: 99%
“…( 22 ) Other more general screening tools can be applied to patients with ESLD, such as emergency‐department PC, which includes three simple criteria: (1) presence of a life‐limiting illness, (2) unmet PC needs (e.g., symptoms, functional decline, frailty, new onset of complications, limited social support), and (3) hospital admissions. ( 36 )…”
Section: Structures and Processes Required For Integrating Nonhospicementioning
confidence: 99%